2015
DOI: 10.4209/aaqr.2015.05.0291
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Level of Polybrominated Diphenyl Ethers in the Home Environment and Assessment of Human Health Risks

Abstract: It has been demonstrated that human exposure to polybrominated diphenyl ethers (PBDEs) might be associated with several adverse health effects. Dietary and microenvironmental sources are considered to be the main routes of PBDEs exposure. The study aimed to investigate PBDEs in residential indoor and outdoor air and further to assess the health risks in family members of different ages. Indoor and outdoor air samples from houses in residential areas were simultaneously collected for analysis of 99, 100, 153, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 47 publications
3
20
2
Order By: Relevance
“…Our value in the outdoor air was only lower than those collected from vehicle parking areas (Li et al, 2016), and in the e-waste storage facilities (Muenhor et al, 2010), and a PRD community (Ding et al, 2016). In comparison with various indoor environments Thuresson et al, 2012;Newton et al, 2015;Shy et al, 2015), indoor air levels of PBDEs in the present study were lower than those in offices, day care centers, and cars, but higher than those in homes and apartments.…”
Section: Resultscontrasting
confidence: 39%
See 4 more Smart Citations
“…Our value in the outdoor air was only lower than those collected from vehicle parking areas (Li et al, 2016), and in the e-waste storage facilities (Muenhor et al, 2010), and a PRD community (Ding et al, 2016). In comparison with various indoor environments Thuresson et al, 2012;Newton et al, 2015;Shy et al, 2015), indoor air levels of PBDEs in the present study were lower than those in offices, day care centers, and cars, but higher than those in homes and apartments.…”
Section: Resultscontrasting
confidence: 39%
“…Both indoor and outdoor levels of PBDEs in the present study were higher than those in Taiwanese home environments (Σ 14 PBDEs: 81.1 and 13.1 pg m -3 in indoor and outdoor air, respectively) (Shy et al, 2015) and ambient air in the rural area of Pingtung (Σ 14 PBDEs: 15.9 pg m -3 ) (Chao et al, 2014c). As compared with other studies published from 2004 to 2016 and shown in Table 2, the mean level of PBDEs in the indoor air in the present study was lower than those in the vehicle parking areas in southern China (Li et al, 2016) and e-waste storage facilities in Thailand (Muenhor et al, 2010), but levels were still higher than those in the domestic environment (Wilford et al, 2004;Takigami et al, 2009;Shy et al, 2015;Ding et al, 2016). Our value in the outdoor air was only lower than those collected from vehicle parking areas (Li et al, 2016), and in the e-waste storage facilities (Muenhor et al, 2010), and a PRD community (Ding et al, 2016).…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations